ANALYTICAL STUDY OF MICROSOMES AND ISOLATED SUBCELLULAR MEMBRANES FROM RAT LIVER : IV. Biochemical, Physical, and Morphological Modifications of Microsomal Components Induced by Digitonin, EDTA, and Pyrophosphate - Amar-Costesec, Alain (The Rockefeller University Press, 1974)
Isopycnic equilibration and sedimentation rate studies of rat liver microsomes led previously to the assignment of microsomal constituents into group a1 (monoamine oxidase), group a2 (5'-nucleotidase, alkaline phosphodiesterase I, alkaline phosphatase and cholesterol), group a3 (galactosyltransferase), group b (NADH cytochrome c reductase, NADPH cytochrome c reductase, aminopyrine demethylase, cytochrome b (5) and P 450), and group c (glucose 6-phosphatase, esterase, nucleoside diphosphatase, β-glucuronidase and glucuronyltransferase). Confirmation and extension of the assignment into groups has been obtained by studying the differential effect of the reagents digitonin, EDTA, and PPi. Digitonin specifically affected the equilibrium density only of the group a2 and (to a lesser extent) group a3, and not of groups b and c under conditions which preserved the structure-linked latency of nucleoside diphosphatase and galactosyltransferase. Within experimental error the rate of sedimentation of all microsomal constituents was unaffected. The morphological appearance under the electron microscope was indistinguishable from that of nondigitonin-treated microsomes, except that a few smooth membranes (< 10%) exhibited broken-looking profiles. Treatment of microsomes with EDTA or PPi detached a substantial part of RNA and released protein in excess over the amount accountable for by detachment of ribosome constituents. This detachment was confirmed by electron microscopy. EDTA and PPi decreased markedly the equilibrium density and the density dispersion of groups b and c, due mainly to the uncoating of rough elements. EDTA and PPi shifted slightly the distribution profiles of groups a towards lower densities, possibly as a result of the release of adsorbed proteins. The combination of EDTA and digitonin, used subsequently, rendered the average equilibrium density of group a2 higher than that of groups b and c. Dense subfractions were thus enriched in constituents of group a2 and showed mainly broken-looking vesicles under the electron microscope. The import of our results on the biochemical and enzymic properties of the subcellular components of the microsome fractions is discussed.